2018
DOI: 10.1177/2325967118805400
|View full text |Cite|
|
Sign up to set email alerts
|

10-Year Epidemiology of Ankle Injuries in Men’s and Women’s Collegiate Basketball

Abstract: Background:Ankle injury is the most common injury in men’s and women’s basketball, regardless of the level of competition.Purpose:To use the National Collegiate Athletic Association (NCAA) Injury Surveillance Program/System (ISP/ISS) to review the 10-year epidemiology of ankle injuries in men’s and women’s collegiate basketball players.Study Design:Descriptive epidemiology study.Methods:The NCAA ISP was queried for men’s and women’s collegiate basketball ankle injury data from the 2004 through 2014 academic ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
2
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 43 publications
1
88
2
2
Order By: Relevance
“…Overall, the percentage time loss longer than 7 days due to ankle injuries in males and females was reported at 29.7 and 32.5 %, respectively. The percentages of time loss longer than 7 days for specific injuries were reported as follows: lateral ligament tear (male, 29.0 %; female, 30.8 %); deltoid ligament tear (male, 18.1 %; female, 24.5 %); anterior tibiofibular syndesmosis sprain (male, 47.3 %; female, 56.7 %) [23]. A systematic review found sex as a potential confounding factor that influenced time to return to play in conservatively treated ankle sprain [24]; however, research on the prognosis of ankle sprain taking sex into account is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the percentage time loss longer than 7 days due to ankle injuries in males and females was reported at 29.7 and 32.5 %, respectively. The percentages of time loss longer than 7 days for specific injuries were reported as follows: lateral ligament tear (male, 29.0 %; female, 30.8 %); deltoid ligament tear (male, 18.1 %; female, 24.5 %); anterior tibiofibular syndesmosis sprain (male, 47.3 %; female, 56.7 %) [23]. A systematic review found sex as a potential confounding factor that influenced time to return to play in conservatively treated ankle sprain [24]; however, research on the prognosis of ankle sprain taking sex into account is not available.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral ligament of the ankle is a key ligament structure to maintain stability of the ankle, and consists of the anterior talofibular ligament (ATFL), calcaneofibular ligament (CFL), and posterior talofibular ligament (PTFL). Due to the anatomical and motor characteristics of the ankle, approximately 85% of the ankle sports injuries are varus injuries, which is damage to the lateral ligament structure, and of which 62% are combined with ATFL injury. Most of the patients with an ankle varus injury can obtain satisfactory results from conservative treatment for 3 to 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the NCAA-ISP has been previously well-described in the literature and will be briefly reviewed. 1 , 3 , 5 , 7 , 9 , 14 , 17 , 22 24 The NCAA-ISP utilizes a voluntary convenience sample of NCAA programs over a 5-year period. Consequently, there is variability in the number of programs participating in the data set each year.…”
Section: Methodsmentioning
confidence: 99%